Exploring User Experience from an Emotional Context When Designing Immersive Games for Education - Tan Chin Ike; Tan Wee Hoe; Julian Lee Eng Kim; Ng Yiing Y’ng (Journal of ICT in Education, 2021)
Abstract In the past decade, the science of learning has taken on a fresh approach through the conceptual incorporation video games. Educational games are now regarded as an effective method to engage the present generation of constantly distracted youths. However, the reality is that many educational games fail to achieve their intended goals as they lack the fun and engagement aspects that is so prevalent in video games. Among the reasons, are that educational games fail to engage the learners. Hence, there is a need for a discourse in the enhancement of engagement aspects in educational games through the understanding of emotional context in user experience (UX). This paper aims to investigate the methods of harnessing emotional-based UX practices from experienced and successful video game designers to make educational games more engaging. Six experienced game designers were interviewed, and the recordings transcribed on verbatim basis to allow for analysis. The outputs of the interview narration were mapped on to UX from an emotional context, explicitly for the design of immersive and engaging gameplay. The findings revealed that UX within the context of game development is a crucial element in creating engaging educational games. The crafting of a good UX allows the game to create an emotional link that learners will experience at various milestones within the game. This link allows for the gameplay experience to effectively control a learners’ emotional state within the game through an immersive game experience. The use of UX can create a strong engagement factor within the game by allowing the players to be absorbed in the game world. In conclusion, to enhance the effectiveness of educational games, game designers should manipulate the learners’ emotion by offering an active role in the narrative structure development of the games; and provoking decision-making scenarios within the game world. Abstrak Dalam dekad yang lalu, sains pembelajaran telah menerokai pendekatan baru melalui penggabungan konsep permainan video. Permainan pendidikan kini difahami sebagai kaedah yang berkesan untuk memenuhi perhatian generasi para pemuda. Namun, kenyataan sebenar adalah kebanyakan permainan pendidikan gagal mencapai tujuan yang diharapkan kerana permainan tersebut tidak melibatkan aspek yang begitu lazim dalam permainan video iaitu dari segi pandangan keseronokan. Antara sebabnya ialah permainan pendidikan gagal melibatkan pelajar. Justeru, terdapat keperluan secara pembicaraan dan penukaran idea secara lisan untuk meningkatkan aspek penglibatan dalam permainan pendidikan melalui pemahaman konteks emosi pengalaman pengguna (UX). Kertas penyelidikan ini bertujuan untuk menyiasat kaedah yang memanfaatkan amalan UX berdasarkan emosi dari pandangan profesional pereka permainan video yang berpengalaman dan telah berjaya untuk menjadikan permainan pendidikan lebih menarik. Enam pereka permainan berpengalaman diwawancarai, dan rakaman ditranskrip berdasarkan kata demi kata untuk membolehkan analisis. Hasil narasi wawancara dipetakan ke UX dari konteks emosi, secara eksplisit dalam reka bentuk permainan yang menarik dan menarik. Hasil kajian menunjukkan bahawa UX dalam konteks pembangunan permainan adalah elemen penting dalam pembentukkan permainan pendidikan yang menarik. Penyusunan UX yang baik membolehkan permainan membuat pautan emosi yang sebenar yang akan dialami pelajar pada setiap langkah dalam permainan. Pautan ini juga membolehkan pengalaman permainan terkawal secara berkesan keatas emosi pelajar dalam permainan melalui pengalaman permainan yang mendalam. Penggunaan UX dapat mewujudkan faktor keterlibatan yang lebih berkesan dalam permainan dengan membiarkan para pemain diserap dalam dunia permainan. Kesimpulannya, untuk meningkatkan keberkesanan permainan pendidikan, pereka permainan harus dengan teliti, memanipulasi emosi pelajar dengan menawarkan peranan aktif dalam struktur naratif permainan; dan memprovokasi senario membuat keputusan dalam dunia permainan.